Caracterização estrutural e funcional de hemoglobinas de skua, Catharacta maccormicki - Landini, Gustavo Fraga (Universidade Federal de São Carlos, 2002)
Hemoglobin samples of Catharacta maccormiki (Skua), an Antarctic bird, collected in winter and in summer were studied. Starch gel eletrophoretic pattern hemoglobin oxygen affinities on blood and stripped hemoglobin; influence of organic phosphates that may change affinity and level of those intra-erythrocytic phosphates were analyzed. No differences were found in Hb-O2 affinities for samples collected in winter and in summer, which leads to believe that migration (Winter) is not a factor for the oxygen affinities in blood. Bohr effect for both situations was practically the same (Φ= -2,1), indicating normal Bohr effect. The 5 samples show a electrophoretic pattern of two components, so, no evidence of intra-specific variation was found. For the stripped hemoglobin the P50 values were inferior to the ones obtained for whole blood, showing a higher affinity for the hemoglobin to oxygen in the absence of possible modulators. The Bohr effect in the alkaline side (pH 7 8) was normal (Φ = -1,9), and in the acid side it was reverse, characteristic of birds hemoglobin. The influence of organic phosphates that could affect oxygen affinity was also tested. 2,3-diphosphoglycerate (2,3DPG) and inositol hexaphosphate (IHP) were added to the stripped hemoglobin in order to test them as modulators. Negative hemoglobin oxygen affinity modulation was observed after addition of both phosphates. IHP is more effective than 2,3DPG. For animal collected during winter only the GTP was present in its erythrocytes, while the summer ones ATP was found instead of GTP. No differences was found in the concentration of inositol penta and hexaphosphsphate in samples collected in the two seasons. No 2,3DPG were found in any sample.
Keywords: Aves; Aves - hemoglobina; Aves antárticas; Fosfatos intraeritrocitários; Eletroforese; Ave - migração; Análise cromatográfica; CIENCIAS BIOLOGICAS::GENETICA